Metastatic potential of melanomas defined by specific gene expression profiles with no BRAF signature - Hoek, Keith; Sucker, Antje; Ugurel, Selma; Kumar, Rajiv; Schadendorf, Dirk (Pigment cell research, 2006)
The molecular biology of metastatic potential in melanoma has been studied many times previously and changes in the expression of many genes have been linked to metastatic behaviour. What is lacking is a systematic characterization of the regulatory relationships between genes whose expression is related to metastatic potential. Such a characterization would produce a molecular taxonomy for melanoma which could feasibly be used to identify epigenetic mechanisms behind changes in metastatic behaviour. To achieve this we carried out three separate DNA microarray analyses on a total of 86 cultures of melanoma. Significantly, multiple testing correction revealed that previous reports describing correlations of gene expression with activating mutations in BRAF or NRAS were incorrect and that no gene expression patterns correlate with the mutation status of these MAPK pathway components. Instead, we identified three different sample cohorts (A, B and C) and found that these cohorts represent melanoma groups of differing metastatic potential. Cohorts A and B were susceptible to transforming growth factor-β (TGFβ)-mediated inhibition of proliferation and had low motility. Cohort C was resistant to TGFβ and demonstrated high motility. Meta-analysis of the data against previous studies linking gene expression and phenotype confirmed that cohorts A and C represent transcription signatures of weakly and strongly metastatic melanomas, respectively. Gene expression co-regulation suggested that signalling via TGFβ-type and Wnt/β-catenin pathways underwent considerable change between cohorts. These results suggest a model for the transition from weakly to strongly metastatic melanomas in which TGFβ-type signalling upregulates genes expressing vasculogenic/extracellular matrix remodelling factors and Wnt signal inhibitors, coinciding with a downregulation of genes downstream of Wnt signalling.